2013
DOI: 10.1186/1742-2094-10-90
|View full text |Cite
|
Sign up to set email alerts
|

3H-Deprenyl and 3H-PIB autoradiography show different laminar distributions of astroglia and fibrillar β-amyloid in Alzheimer brain

Abstract: BackgroundThe pathological features in Alzheimer’s disease (AD) brain include the accumulation and deposition of β-amyloid (Aβ), activation of astrocytes and microglia and disruption of cholinergic neurotransmission. Since the topographical characteristics of these different pathological processes in AD brain and how these relate to each other is not clear, this motivated further exploration using binding studies in postmortem brain with molecular imaging tracers. This information could aid the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 66 publications
(77 reference statements)
9
53
0
Order By: Relevance
“…The biochemical quantification of GFAP with ELISA confirmed the results obtained with immunohistochemistry and indicated that increased GFAP levels were a consequence of, or at least mirrored, the Aβ accumulation. These results are also supported by the previous studies in APP swe mice and on post mortem human brain tissue [30,42]. Another preclinical study, conducted in APP/PS1 mice, focusing on GABA function reported low degree of co- localization of MAO-B and GFAP [43].…”
Section: Discussionsupporting
confidence: 83%
“…The biochemical quantification of GFAP with ELISA confirmed the results obtained with immunohistochemistry and indicated that increased GFAP levels were a consequence of, or at least mirrored, the Aβ accumulation. These results are also supported by the previous studies in APP swe mice and on post mortem human brain tissue [30,42]. Another preclinical study, conducted in APP/PS1 mice, focusing on GABA function reported low degree of co- localization of MAO-B and GFAP [43].…”
Section: Discussionsupporting
confidence: 83%
“…Astrocytosis shows a spatial and temporal pattern different from both fibrillar amyloid and cerebral glucose metabolism [14]. In vitro autoradiography studies with 3 H-deprenyl show higher labeling in the superficial layers in comparison to binding in the deeper layers of the frontal AD cortices [15]. This is in agreement with earlier findings of gliosis in different cortical layers [16].…”
Section: Inflammatory Changes In Brains Of Sporadic Ad Patientssupporting
confidence: 81%
“…This is in agreement with earlier findings of gliosis in different cortical layers [16]. High binding of 3 H-deprenyl is found in all hippocampal subregions [15]. The fibrillar Aβ 3 H-PIB binding is high in all frontal cortical layers and low in the hippocampus [15].…”
Section: Inflammatory Changes In Brains Of Sporadic Ad Patientssupporting
confidence: 81%
See 1 more Smart Citation
“…Combined with the observation that cholinergic neurons degenerate and nAChR levels are decreased in AD (Auld et al, 2002;Marutle et al, 2013;Okada et al, 2013), the above results suggest that the interaction between nAChRs and Aβ 1-42 affects cognitive function and may be involved in the pathophysiology of Alzheimer's disease.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 77%